Chemosensitization of Plant Pathogenic Fungi to Agricultural Fungicides - Dzhavakhiya, Vitaly; Shcherbakova, Larisa; Semina, Yulia; Zhemchuzhina, Natalia; Campbell, Bruce (Frontiers in Microbiology, 2012)
A common consequence of using agricultural fungicides is the development of resistance by fungal pathogens, which undermines reliability of fungicidal effectiveness. A potentially new strategy to aid in overcoming or minimizing this problem is enhancement of pathogen sensitivity to fungicides, or “chemosensitization.” Chemosensitization can be accomplished by combining a commercial fungicide with a certain non- or marginally fungicidal substance at levels where, alone, neither compound would be effective. Chemosensitization decreases the probability of the pathogen developing resistance, reduces the toxic impact on the environment by lowering effective dosage levels of toxic fungicides, and improves efficacy of antifungal agents. The present study shows that the antifungal activity of azole and strobilurin fungicides can be significantly enhanced through their co-application with certain natural or synthetic products against several economically important plant pathogenic fungi. Quadris (azoxystrobin) combined with thymol at a non-fungitoxic concentration produced much higher growth inhibition of Bipolaris sorokiniana, Phoma glomerata, Alternaria sp. and Stagonospora nodorum than the fungicide alone. The effect of Dividend (difenoconazole) applied with thymol significantly enhanced antifungal activity against B. sorokiniana and S. nodorum. Folicur (tebuconazole) combined with 4-hydroxybenzaldehyde (4-HBA), 2,3-dihydroxybenzaldehyde or thymol significantly inhibited growth of A. alternata, at a much greater level than the fungicide alone. In addition, co-application of Folicur and 4-HBA resulted in a similar enhancement of antifungal activity against Fusarium culmorum. Lastly, we discovered that metabolites in the culture liquid of F. sambucinum biocontrol isolate FS-94 also had chemosensitizing activity, increasing S. nodorum sensitivity to Folicur and Dividend.